Character Values In The Local Tradition Of Syariful Anam In The Malay Community Of The Riau Island - zaitun zaitun zaitun; Siti Habiba habiba (At-Tarbiyat, 2021)
This study examines the character values ​​that exist and is contained in the syariful anam tradition of the Malay people of the Riau Archipelago. The syariful anam tradition is a unique tradition that combines religious elements and cultural elements of the Riau Archipelago Malay community, which has been carried out for generations. The practice of syariful anam is a hair cut procession or haircut for babies who have not yet entered the age of 2 years. The religious element contained in this tradition is the reading of praise or community poetry and barzanji of the Prophet Muhammad SAW. The cultural component of this tradition is the activity of white flour. The haircutting process for the child is carried out at home or in a room. A small piece of hair is put in a container, and the child is carried or supported by his family to the nearest mosque accompanied by the recitation of barzanji in response; then, the child will be sprinkled with plain flour. Implementing the Syariful Anam tradition is held on the anniversary of one of the essential Islamic days, the Birthday of the Prophet Muhammad. This research method is field research by conducting observations, distributing questionnaires with participants, and conducting interviews with community leaders and elders who understand this syariful anam tradition, then analyzing all the data collected and describing the findings. The content of character values ​​in this syariful anam tradition includes the importance of faith and Islamic worship, belief in prophets and apostles, the value of gratitude to Allah SWT, servitude, surrender, obedience, respect, maintaining cleanliness, helping others. , tenacious, patient, challenging, and independent.